Didactic suitability criteria in a Lesson Study-based class - Hummes, Viviane Beatriz; Breda, Adriana; Seckel, María José; Font, Vicenç (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This study seeks to identify the didactic suitability criteria used by a group of teachers in a training process of a class—design, implementation, and reflection/redesign—carried out under an experience of lesson study. The didactic suitability tool is used for qualitative analysis. It is concluded that the group of teachers implicitly uses some of the components and indicators of didactic suitability. In particular, the interactional and cognitive criteria are used in a more comprehensive way and, in a less detailed manner, the epistemic and emotional criteria. Furthermore, the means and ecological criteria are rarely used in the group's reflection.